Foreign aid and democratic development in Africa - Simone Dietrich; Joseph Wright (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Over the past two decades, donors increasingly linked foreign aid to democracy objectives in sub-Saharan Africa. Yet systematic research on this topic typically focuses on how aid influences democratic transitions. This study investigates whether and how foreign aid affects the process of democratic consolidation in sub-Saharan Africa by examining two potential mechanisms: (1) the use of aid as leverage to buy political reform, and (2) investment in the opposition. We test these mechanisms using five dependent variables that capture different aspects of democratic consolidation. Using survival analysis for the period from 1991 to 2008, we find that democracy and governance aid has a consistently positive effect on democratic consolidation. Economic aid, on the other hand, has no effect on democratic consolidation.
Keywords: C41; D72; F35; N47; 330; Africa; democratic consolidation; foreign aid; survival analysis; Entwicklungshilfe; Demokratisierung; Afrika